2020
DOI: 10.4081/ecj.2020.9017
|View full text |Cite
|
Sign up to set email alerts
|

Lung ultrasound in COVID-19: a useful diagnostic tool

Abstract: Coronavirus disease 2019 (Covid-19), caused by a novel enveloped RNA betacoronavirus, has recently been declared a public health emergency by the World Health Organization (WHO). The lack of knowledge at the beginning of the pandemics, associated with the inherent risk of infective spreading, makes initial recognition and management particularly complex, in terms of defining effective diagnostic and therapeutic protocols. In the Emergency setting, Lung Ultrasound (LUS) can play an important role in the managem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 18 publications
0
20
0
Order By: Relevance
“…29,30 Musolino et al used "Soldati LUS protocol" for lung ultrasound examinations, whereas Denina et al used the Copetti protocol. 20,21 In both of these pediatric surveys vertical artifacts, areas of white lung, subpleural consolidations and pleural irregularities were the main findings in children with COVID-19 pneumonia; no cases of pleural effusions were detected. 29,30 Denina et al reported only one case (out of 8 children) of discordance of LUS and chest x-ray results, respectively with B-lines pattern and normal radiological imaging.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…29,30 Musolino et al used "Soldati LUS protocol" for lung ultrasound examinations, whereas Denina et al used the Copetti protocol. 20,21 In both of these pediatric surveys vertical artifacts, areas of white lung, subpleural consolidations and pleural irregularities were the main findings in children with COVID-19 pneumonia; no cases of pleural effusions were detected. 29,30 Denina et al reported only one case (out of 8 children) of discordance of LUS and chest x-ray results, respectively with B-lines pattern and normal radiological imaging.…”
Section: Discussionmentioning
confidence: 88%
“…The adult studies suggested similar findings: thickening of the pleural line with pleural line irregularity ( Figure 4); B lines: focal ( Figure 5), multifocal ( Figure 6), confluent ( Figure 7); subpleural consolidations (Figure 8), in a variety of patterns including multifocal small, nontranslobar and translobar with occasional mobile air bronchograms; pleural effusion is uncommon. 9,[11][12][13][14][15][16][17][18] In light of these findings researchers have proposed 4 patterns considering the loss of aeration: 21 pattern 0: presence of A-lines or up to 2 different B-lines instead of A lines. pattern 1: 3 or more evident B-lines.…”
Section: Resultsmentioning
confidence: 99%
“…Such movements are linked to pleural sliding. The (1,2,5,6) are delimited medially by the hemi-clavicular line and laterally by the anterior axillary line whereas the lateral ones (3,4,7,8) are included between the anterior and posterior axillary lines. The sub-mammary line divides the upper and lower zones.…”
Section: Pneumothoraxmentioning
confidence: 99%
“…We lacked on-site diagnostic capacity, so as I worked to secure critical resources to improve over all care, I also sought and received approval to incorporate point-of-care ultrasonography" [1]. These claims are so much actually in these days of Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-COV-2) pandemic spread so that LUS seems to be strongly adapting to the follow-up for lung involvement of patients with ascertaining Coronavirus up to, in our opinion emblematic, use of LUS at the emergency triage or at home medical visit as a screening imaging test of suspected COVID-19 patients [2][3][4]. If on one hand, many studies have shown the efficacy of LUS in diagnosing pulmonary pathology, with increased sensitivity compared to that of chest X-ray (CXR) [5][6][7], on the other hand, little is discussed about its limits and pitfalls especially in generic and off label clinical contest.…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, lung ultrasound is a radiation-free test, making it suitable for special populations, particularly desirable for pregnant women. 67,68 Kalafat et al, reported on a case involving a pregnant woman who initially tested negative using RT-PCR, but was later found to be positive through lung ultrasound. This demonstrates the potential for lung ultrasound to play an important role in the triage of pregnant women with suspected COVID-19.…”
Section: Lung Ultrasoundmentioning
confidence: 99%